Morphological and Productive Correlations of Cutting Pennisetum Varieties Under Conditions of Peruvian Humid Tropics - Pinchi-Carbajal, S. F.; Quispe-Ccasa, H. A.; Ampuero-Trigoso, G.; Nolasco-Lozano, E.; Saucedo-Uriarte, J. A. (Tropical Animal Science Journal, 2024)
Livestock farming in the Peruvian tropics is based on the use of grazing forage, but cutting grasses offers greater productivity and seasonality advantages. In this study, the morphological and productive characteristics of King Grass Morado (KGM), Cuba OM-22 (CU), and Maralfalfa (MA) were evaluated and correlated with chlorophyll content under Peruvian humid tropic conditions. Five plots of 1 ha each were installed for the three Pennisetum varieties (2-1-2), with three samples per plot. No significant differences were found in plant height, leaf length, number of nodes, number of leaves/stem, number of stems, stem circumference, length of nodes, leaf, stems, and total weight, chlorophyll index (atLEAF CLOR), performance index (API), and dry matter. KGM stood out in tillering (12.86) (p